Usual walking and obstacle avoidance are influenced by depressive and anxiety symptoms in patients with Parkinson's disease - Nóbrega-Sousa, Priscila [UNESP]; Orcioli-Silva, Diego [UNESP]; Lirani-Silva, Ellen [UNESP]; Beretta, Victor Spiandor [UNESP]; Vitório, Rodrigo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Wiley, 2019)
Aim: The aim of the present study was to analyze the association of depressive and anxiety symptoms with usual walking and obstacle avoidance in patients with Parkinson's disease. Methods: Patients were divided into three groups: without depressive and anxiety symptoms (n = 28); depressive symptoms only (n = 15); and depressive and anxiety symptoms (n = 19). Symptoms of depression and anxiety were evaluated by the Hospital Anxiety and Depression scale. Participants walked across a pathway in two experimental conditions: usual walking and obstacle avoidance. Kinematic data were recorded using an optoelectronic three-dimensional system. Results: During usual walking, the depressive and anxiety symptoms group presented shorter stride length and longer double support phase compared with the without depressive and anxiety symptoms group, and lower velocity than the without depressive and anxiety symptoms and depressive symptoms groups. During the approach phase of obstacle avoidance, the depressive and anxiety symptoms group decreased the stride length and velocity, whereas the without depressive and anxiety symptoms and depressive symptoms groups did not modulate these parameters. The depressive and anxiety symptoms group also showed shorter step length and velocity, longer step duration, and wider step width during obstacle crossing. Additionally, the depressive and anxiety symptoms group presented shorter foot-to-obstacle horizontal distances, and lower horizontal mean velocities during obstacle crossing. Partial correlation analyses showed that both depressive and anxiety symptoms were associated with spatiotemporal gait parameters. Conclusion: Combined symptoms of depression and anxiety are associated with walking impairments in patients with Parkinson's disease in both usual walking and obstacle avoidance. Geriatr Gerontol Int 2019; 19: 868–873.
Keywords: adaptive walking; gait; movement disorders; non-motor symptoms; Parkinson's disease